Molecular Imaging of Hypoxia-Inducible Factor 1α and von Hippel-Lindau Interaction in Mice - Clara Y.H. Choi; Denise A. Chan; Ramasamy Paulmurugan; Patrick D. Sutphin; Quynh-Thu Le; Albert C. Koong; Wayne Zundel; Sanjiv S. Gambhir; Amato J. Giaccia (Molecular Imaging)
Tumor hypoxia plays a crucial role in tumorigenesis. Under hypoxia, hypoxia-inducible factor 1α (HIF-1α) regulates activation of genes promoting malignant progression. Under normoxia, HIF-1α is hydroxylated on prolines 402 and 564 and is targeted for ubiquitin-mediated degradation by interacting with the von Hippel-Lindau protein complex (pVHL). We have developed a novel method of studying the interaction between HIF-1α and pVHL using the split firefly luciferase complementation-based bioluminescence system in which HIF-1α and pVHL are fused to amino-terminal and carboxy-terminal fragments of the luciferase, respectively. We demonstrate that hydroxylation-dependent interaction between the HIF-1α and pVHL leads to complementation of the two luciferase fragments, resulting in bioluminescence in vitro and in vivo. Complementation-based bioluminescence is diminished when mutant pVHLs with decreased affinity for binding HIF-1α are used. This method represents a new approach for studying interaction of proteins involved in the regulation of protein degradation.